Impact of Social Movements on Renewable Energy Policy in Indonesia: Study of Solar Power Plants - T. Agung Kurniawan; Yanif Dwi Kuntjoro; Purnomo Yoesgiantoro; Habibie Satrio Nugroho (CV. AFDIFAL MAJU BERKAH, 2024)
Anthropogenic-induced warming has altered the climate of the Earth, causing significant impacts on urban areas such as compromised water supplies and detrimental health effects. This paper employs a case study approach to analyse the causal relationship between energy consumption and social activities. Such an approach is well-suited to unraveling complex cause-and-effect relationships or pathways. System mapping is a method used in case study research to analyse cause-and-effect relationships in complex systems, such as energy systems. The primary literature was searched utilising the reverse snowball technique, with a focus on renewable energy, particularly solar power. Its importance is highlighted in global efforts to reduce dependence on fossil fuels and mitigate the effects of climate change. Indonesia has extensive solar potential and is preparing to utilise solar energy as a clean power source. Nonetheless, effective policy implementation necessitates more than governmental intention; active participation from social movements is required. Two prominent movements - the Solar Electricity Initiative Movement and the Million Solar Roof National Movement - are significant driving forces in this pursuit. The Role of Social Movements in Environmental Policy Transition to Renewable Energy Sources. Social Movements are instrumental in promoting renewable energy policies through public awareness campaigns, advocacy, and concrete actions. They are essential in accelerating policy changes and facilitating a transition towards clean energy. In light of the challenges posed by climate change, the hard work of social movements has become increasingly significant in achieving Indonesia's goal of becoming a sustainable country that does not rely on fossil fuels.